2022
DOI: 10.5546/aap.2022.eng.39
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent behaviors during the preventive and mandatory social isolation in Argentina in 2020

Abstract: Introduction. In March 2020, Argentina established a preventive and mandatory social isolation policy (ASPO, for its acronym in Spanish) due to the COVID-19 pandemic. Objective. To explore the behaviors and habits of the adolescent population during the ASPO and the extent of compliance. Population and methods. Qualitative and quantitative, cross sectional study in Argentine adolescents aged 12-20 years. An anonymous, semi-structured questionnaire was administered during epidemiological weeks 34 to 36. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…To date, research regarding the impacts of the pandemic on youth substance use has been quite inconsistent, including among studies that have used designs and combined measures of alcohol or drug use (e.g., cannabis, illicit drugs, non-prescribed use of prescription drugs, etc) similar to our study [ 9 ]. For instance, one cross-sectional study measuring alcohol, cannabis, or drug use, reported an increase in alcohol and non-specified drug use during the pandemic [ 23 ], while another reported less alcohol, cannabis and other drug use [ 24 ]. To our knowledge, two other studies [ 25 , 26 ] have used the same validated outcome measure (i.e., GAIN-SS for past 30 days) as in our study.…”
Section: Discussionmentioning
confidence: 99%
“…To date, research regarding the impacts of the pandemic on youth substance use has been quite inconsistent, including among studies that have used designs and combined measures of alcohol or drug use (e.g., cannabis, illicit drugs, non-prescribed use of prescription drugs, etc) similar to our study [ 9 ]. For instance, one cross-sectional study measuring alcohol, cannabis, or drug use, reported an increase in alcohol and non-specified drug use during the pandemic [ 23 ], while another reported less alcohol, cannabis and other drug use [ 24 ]. To our knowledge, two other studies [ 25 , 26 ] have used the same validated outcome measure (i.e., GAIN-SS for past 30 days) as in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The risk factors for the development of loneliness include social isolation. Thus, the COVID-19 pandemic’s confinement has increased loneliness among young people [ 2 , 7 ], especially those living in disadvantaged districts [ 8 ]. COVID-19 has also influenced feelings of sadness [ 7 , 9 , 10 ] and “feeling like crying all the time” [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the COVID-19 pandemic’s confinement has increased loneliness among young people [ 2 , 7 ], especially those living in disadvantaged districts [ 8 ]. COVID-19 has also influenced feelings of sadness [ 7 , 9 , 10 ] and “feeling like crying all the time” [ 11 ]. The same results were obtained in a study of Brazilian adolescents aged 15–18 years, noting that confinement was associated with increased feelings of sadness, anxiety and loneliness in young people [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the COVID-19 pandemic has raised huge concerns for the mental health of an entire generation of children and young people ( 7 ), which may be related to the adoption of anti-epidemic measures such as lockdown, school closure, and social distancing. Mandatory social distancing policies have reduced the accessibility of drugs, and adolescents' drug use has decreased ( 8 , 9 ); while subsequent small-scale unblocking might bring about experimental drug use among adolescents. Drug use have become a public health issue with a serious impact on people's development and social security.…”
Section: Introductionmentioning
confidence: 99%